Analysis of Public Perspective on the Use of Artificial Intelligence Technology in Public Services in Indonesia - Hamzah, Nur Azizah (Moccasin Journal De Public Perspective, 2024)
This study explores public perspectives on artificial intelligence (AI) use in government services, focusing on trust, transparency, and ethical governance as pivotal factors for public acceptance. Using both quantitative surveys and qualitative interviews, the research identifies a strong correlation between public understanding of AI’s functions and support for its application in critical areas such as healthcare and law enforcement. The findings reveal that public trust hinges on transparent government practices, ethical accountability, and citizen engagement in AI policymaking. Additionally, the study highlights the need for AI literacy programs and workforce reskilling initiatives to prepare citizens for an AI-driven future, emphasizing continuous evaluation and public consultation to ensure ethical alignment. Recommendations underscore collaborative efforts in education, regulatory frameworks, and ethical oversight as essential to fostering a balanced approach to AI adoption.